Enhancing organisational resilience through systems thinking - Dumisani Manzini; Rudolph Oosthuizen; Hilda Chikwanda (Social Sciences and Humanities Open)
In the face of complex challenges driven by technological advancements and global crises, organisations must develop better strategies for survival and sustainability. The paper introduces a conceptual model for measuring and assessing organisational resilience rooted in systems thinking (ST) methodologies. It is tailored to service organisations, addressing disruptions caused by digital transformation (DT). The study employs a PRISMA protocol to review articles from academically respected research databases. A total of 155 documents were included in the final analysis to compile the research paper. The systematic literature review (SLR) identified crucial dimensions of organisational resilience, their interrelationships, and the gap in developing a resilience framework for the service industry. These are captured in a graphical conceptual model using ST tools as a novel method to show the key organisational resilience dimensions and their interactions. A Systemigram holistically visualises the complex structure of organisational resilience dimensions and their interconnections. This structure supported the development of a conceptual causal loop diagram (CLD) that illustrates how DT drives environmental disruption, impacting organisation's stability and resilience. These dynamic internal and external changes driven by technology, innovation, and evolving customer needs influence organisational resilience. This proposed framework can aid organisations in making informed strategic decisions to improve resilience and a sustainable future.